1979
DOI: 10.1139/o79-143
|View full text |Cite
|
Sign up to set email alerts
|

From β-lipotropin to β-endorphin and 'pro-opio-melanocortin'

Abstract: Studies on the biosynthesis of beta-LPH on the one hand, and of ACTH on the other, have produced a new concept, that of a single precursor form which contains three active molecules. Thus, it is proper to name such a precursor 'pro-opio-melanocortin.' The concept that beta-LPH was a precursor molecule was first put forward in 1967 and was based on both structural forms and biological activities. The discovery that morphine-like substances are part of the C-terminal fragment of beta-LPH brought an additional im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
33
0

Year Published

1980
1980
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(35 citation statements)
references
References 24 publications
2
33
0
Order By: Relevance
“…These composite precursors bear a close resemblance to viral polyproteins [7] which also comprise several distinct functional products. To date, direct evidence for such cellular polyproteins [8], in the form of amino acid sequence, is only available for pro-opiocortin [ 1,9] which consists of corticotropin, /3-lipotropin, endorphins and melanotropins. However, indirect evidence points to the existence of similar composite precursors in the hypothalamus, namely the common precursors to arginine vasopressin/neurophysin II and oxytocin/ neurophysin I.…”
Section: Introductionmentioning
confidence: 99%
“…These composite precursors bear a close resemblance to viral polyproteins [7] which also comprise several distinct functional products. To date, direct evidence for such cellular polyproteins [8], in the form of amino acid sequence, is only available for pro-opiocortin [ 1,9] which consists of corticotropin, /3-lipotropin, endorphins and melanotropins. However, indirect evidence points to the existence of similar composite precursors in the hypothalamus, namely the common precursors to arginine vasopressin/neurophysin II and oxytocin/ neurophysin I.…”
Section: Introductionmentioning
confidence: 99%
“…The maps showed that the primary structures of the two forms of pro-opiomelanocortin differ in at least two parts of the molecules, one part concerning the endorphin region Extensive biosynthetic investigations with a mouse adrenocorticotropic tumor cell line have provided evidence for the existence of a common precursor to corticotropin and /3-lipotropin [l]. Studies concerning the pars intermedia of the pituitary gland revealed the occurrence in this tissue of a similar prohormone, which was named pro-opiomelanocortin [2]. In the pars intermedia this prohormone is processed to peptides related to a-melanotropin, corticotropin and endorphin [3 -61.…”
mentioning
confidence: 99%
“…Studies concerning the pars intermedia of the pituitary gland revealed the occurrence in this tissue of a similar prohormone, which was named pro-opiomelanocortin [2]. In the pars intermedia this prohormone is processed to peptides related to a-melanotropin, corticotropin and endorphin [3 -61.…”
mentioning
confidence: 99%
“…In the pars intermedia the same prohormone functions as the precursor for a-melanotropin, corticotropinlike intermediate lobe peptide [corticotropin-(I 8 -39)], and /I-endorphin ; it was, therefore, named pro-opiomelanocortin [2]. Nakanishi et al [3] revealed the nucleotide sequence of the cloned cDNA, which is complementary to the mRNA that codes for pro-opiomelanocortin in bovine pituitary glands.…”
mentioning
confidence: 99%